Comparison Performances of VoIP in Various Network Topologies - Junaedi Adi Prasety (International Conference on Industrial Revolution for Polytechnic Education, 2019)
VoIP is a digital communication technology thatis currently developing in this decade. This technology isdeveloping because VoIP can be implemented on computernetworks. So, by converting analog voice into packets, the voicecan be sent using computer networks. Nowadays, computernetworks have various kinds of topologies such as bus, star, ringand mesh. Each of these topologies has advantages anddisadvantages. In this research, VOIP was implemented andafter that the performance measurements were carried out foreach of the topologies. The VoIP server used is an Elastix serverand for implementing network topologies using access points.The results of this research are expected to be used as areference in the implementation of VoIP in several types oftopologies.